Pengaruh Kesiapan Konseling (Readiness) Terhadap Proses Konseling - Karunia, Marpren; Karneli, Yeni; M, Mudjiran (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Counseling readiness is a key factor that influences the effectiveness of the counseling process, encompassing an individual's awareness, commitment, and openness to the counselor's help. This study aims to explore the influence of counseling readiness on counseling success and strategies to optimize it. Through a literature review, it was found that individuals with high counseling readiness tend to be more open, have low anxiety levels, and are able to receive feedback constructively. Internal factors such as motivation and emotional stability, as well as external factors such as social support and learning environment, strongly influence this readiness. Conversely, lack of preparedness can result in resistance, low effectiveness and negative impacts on mental health. Proposed strategies include education, strengthening the counselor-client relationship, and initial assessment. This study confirms that counseling readiness is an integral element that determines the success of the counseling process and needs to be improved to support individuals' optimal mental health.